Patients’ perspectives on prescription cannabinoid therapies: a cross-sectional, exploratory, anonymous, one-time web-based survey among German patients - Fischer, Jan Moritz; Kandil, Farid I.; Katsarova, Ekaterina; Zager, Laura Sophie; Jeitler, Michael; Kugler, Felix; Fitzner, Franziska; Murthy, Vijayendra; Hanslian, Etienne; Wendelmuth, Christoph; Michalsen, Andreas; Karst, Matthias; et al. (Frontiers in Medicine, 2023)
Introduction Since cannabinoids were partially legalized as prescription medicines in Germany in 2017, they are mostly used when conventional therapies do not suffice. Ambiguities remain regarding use, benefits and risks. This web-based survey explored the perspectives of patients whose experiences are not well enough known to date. Methods In an anonymous, exploratory, cross-sectional, one-time web-based observational study, participants receiving cannabinoid therapy on prescription documented aspects of their medical history, diagnoses, attitudes toward cannabinoids, physical symptoms, and emotional states. Participants completed the questionnaires twice here: first regarding the time of the survey and then, retrospectively, for the time before their cannabinoid therapy. Participants were recruited in a stratified manner in three German federal states. Results N = 216 participants (48.1% female, aged 51.8 ± 14.0) completed the survey, most of which (72%, n = 155) reported pain as their main reason for cannabinoid therapy. When comparing the current state with the retrospectively assessed state, participants reported greater satisfaction with their overall medical therapy (TSQM II: +47.9 ± 36.5, p < 0.001); improved well-being (WHO-5: +7.8 ± 5.9, p < 0.001) and fewer problems in PROMIS subscales (all p < 0.001). Patients suffering primarily from pain (72%, n = 155) reported a reduction of daily pain (NRS: −3.2 ± 2.0, p < 0.001), while participants suffering mainly from spasticity (8%, n = 17) stated decreased muscle spasticity (MSSS: −1.5 ± 0.6, p < 0.001) and better physical mobility (−0.8 ± 0.8, p < 0.001). Data suggests clinically relevant effects for most scores. Participants’ attitudes toward cannabinoids (on a 5-point scale) improved (+1.1 ± 1.1, p < 0.001). Most patients (n = 146, 69%) did not report major difficulties with the cannabinoid prescription process, while (n = 27; 19%) had their cannabinoid therapy changed due to side effects. Discussion Most participants experienced their therapy with cannabinoids as more effective than their previous therapy. There are extensive limitations to this cross-sectional study: the originally intended representativeness of the dataset was not reached, partly due to the SARS-CoV-2 pandemic; the sample has a larger proportion of privately insured and self-paying patients. Results does not suggest that cannabinoid patients belong to a particular clientele. Effect sizes observed for pain reduction, quality of life, social participation, and other outcomes suggest a therapeutic potential, particularly in the treatment of chronic pain.